Faktor–Faktor yang Berhubungan dengan Gejala Sick Building Syndrome (SBS) pada Pekerja Staff di Gedung Operasional PT. XYZ Tahun 2024 - Gina Sonia; Eka Cempaka Putri; Desyawati Utami; Putri Handayani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
This study aims to determine the factors associated with Sick Building Syndrome (SBS) symptoms in staff workers at the PT. XYZ operational building in 2024. The study was conducted from November 2024 to January 2025 using a quantitative method with a cross-sectional study design. The population in this study was 70 staff workers in 13 workspaces. The sampling technique used was total sampling. Data were collected through questionnaires and observations, including SBS symptoms, room temperature, and humidity measurements. The results showed that 48 staff workers (71.6%) experienced SBS symptoms. The Chi-square test results showed no relationship between temperature and humidity with SBS in staff workers at the PT. XYZ Operational Building. In conclusion, there is no relationship between temperature and humidity with SBS in staff workers at the PT. XYZ Operational Building. Suggestions from this study include ensuring the commitment made regarding the improvement of the AC system and consistent room maintenance, implementing policies on the role of HSE, and further research is expected to include variables such as air quality factors, microbiological factors, and chemical factors in the room to detect sources of contamination suspected of being related to SBS.